Value of the Dorsal Cutaneous Guinea Pig Model in Selecting Topical Antiviral Formulations for the Treatment of Recurrent Herpes simplex Type 1 Disease - Poli, Giorgio; Dall’Ara, Paola; Binda, Sandro; Santus, Giancarlo; Poli, Alberto; Cocilovo, Alessandra; Ponti, Wilma (Arzneimittelforschung, 2001)
Recurrent herpes simplex labialis represents a disease still difficult to treat, despite the availability of many established antiviral drugs used in clinical research since 30 years ago. Although differences between the human disease and that obtained in experimental animal suggest caution in predicting an effective clinical response from the experimental results, some of the animal models seem to be useful in optimising the topical formulation of single antiviral drugs.In the present work the dorsal cutaneous guinea pig model was used to compare 5 different topical antiviral formulations with clinical promise (active molecule: 5 % w/w micronized aciclovir, CAS 59277-89-3), using both roll-on and lipstick application systems. The aim being to evaluate which vehicle (water, oil, low melting and high melting fatty base) and application system (roll-on, lipstick) enhances the skin penetration and the antiviral activity of the drug, after an experimental intradermal infection with Herpes simplex virus type 1 (HSV-1). As reference, a commercial formulation (5 % aciclovir ointment) was used.The cumulative results of this study showed that the formulation A, containing 5 % aciclovir in an aqueous base in a roll-on application system, has the better antiviral efficacy in reducing the severity of cutaneous lesions and the viral titer; among the lipsticks preparations, the formulation D, containing 5 % aciclovir in a low melting fatty base, demonstrates a very strong antiviral activity, though slightly less than formulation A.This experimental work confirms the validity of the dorsal cutaneous guinea pig model as a rapid and efficient method to compare the antiviral efficacy of new formulations, with clinical promise, to optimise the topical formulation of the active antiviral drugs.
Keywords: Aciclovir, antiviral efficacy, dorsal cutaneous guinea pig model, topical formulations; Antiviral drugs; CAS 59277-89-3